Urban Natural Burial: Re-presenting Data as a Means of Communicating New Approaches to Green Infrastructure - Ian Fisher; Ann Sharrock (Fábos Conference on Landscape and Greenway Planning, 2016)
The authors have published a number of articles (Ian Fisher and Ann Sharrock, 2013, 2014) and have received media coverage on their proposals for linking natural burial, urban microclimate modification and the revaluing of privately owned urban “hope value” land. The purpose of this paper is to further explore the ideas advanced in the author’s research and their potential as formative elements in green infrastructure. To facilitate this process, the authors intend to analyse and test the medium of info graphics as a vehicle for communicating the assembled but separate empirical evidence as a means of supporting the validity of their research. The authors feel that this approach could not only convincingly display potential performative aspects in a more legible format, but also “uncover realities previously unseen or unimagined.” (James Corner 1999)
Keywords: greenways; burial; cemetery; green infrastructure; natural; green